The electromagnetic spectrum [videorecording (DVD)]. (Start smart. Science I need to know., 2014)
A unique program that introduces electromagnetic waves, their behaviors, and how scientists visualize this data. Each region of the spectrum is described and illustrated with engaging examples. Learn about Radio Waves, Microwaves, Infrared Waves, Visible Light Waves, Ultraviolet Waves, X-Rays, and Gamma Waves. Come and explore the amazing world beyond the visible!